Criminal Law in Muslim-Majority Countries: Balancing Sharia, Human Rights, and Global Standards - Nasoha, Ahmad Muhamad Mustain; Atqiya, Ashfiya Nur; Abdullah, Imam; Ukasyah, Muhammad Nur; Assaifi, Viror Ghufron (SHAHIH: Journal of Islamicate Multidisciplinary, 2025)
This study examines the harmonization of Islamic law (shariah) with international human rights standards, focusing specifically on criminal law in Muslim-majority countries. It investigates critical themes such as gender rights, religious freedom, and the administration of criminal justice through analytical and comparative methodologies. Central to the discussion is the application of maqasid al-syariah(objectives of Islamic law) as a dynamic framework to reinterpret Shariah in ways that align with global human rights norms. The findings underscore that while significant challenges persist, several Muslim-majority countries are embracing legal reforms inspired by maqasid al-syariah, particularly in areas like gender-sensitive laws and criminal justice reforms. Education and awareness campaigns emerge as pivotal for fostering a more nuanced understanding of the relationship between Shariah and human rights among scholars, policymakers, and the general public. The study emphasizes the importance of sustained dialogue between religious scholars, human rights advocates, and legal practitioners. It further recommends government initiatives to institutionalize legal reforms, integrate human rights education into national curricula, and establish frameworks for ongoing interfaith and intercultural discourse. Ultimately, the research concludes that harmonizing Shariah with global human rights standards is both feasible and essential. Achieving this balance will require collaborative efforts from all stakeholders to establish legal systems that uphold Islamic principles while ensuring the protection of individual rights. Such efforts not only enhance justice within Muslim-majority countries but also reinforce the universal applicability of Islamic values in a diverse and pluralistic global society.